Psychobiotic Supplementation of PS128TM Improves Stress, Anxiety, and Insomnia in Highly Stressed Information Technology Specialists: A Pilot Study - Wu, Shu-I; Wu, Chien-Chen; Tsai, Pei-Joung; Cheng, Li-Hao; Hsu, Chih-Chieh; Shan, Ian-Kai; Chan, Po-Ying; Lin, Ting-Wei; Ko, Chih-Jung; Chen, Wan-Lin; Tsai, Ying-Chieh (Frontiers in Nutrition, 2021)
Background: Information technology (IT) is an industry related to the production of computers, information processing, and telecommunications. Such industries heavily rely on the knowledge and solutions provided by IT specialists. Previous reports found that the subjective stress scores were higher in IT specialists who developed diabetes, hypertension, and depression. Specific probiotics, known as psychobiotics, may alleviate stress and mood symptoms. This study aimed to examine whether an 8-week intervention of a novel psychobiotic, Lactobacillus plantarum PS128TM (PS128TM), improved self-perceived stress and mood symptoms among high-stress IT specialists. Methods: This open-label, single-arm, baseline-controlled study included IT specialists from a large IT company in Northern Taiwan. Participants with a Perceived Stress Scale (PSS) 10-item version score of 27 or higher were included. Participants were asked to take two capsules containing PS128TM powder, equivalent to 20 billion colony-forming units, daily. Self-report measures, such as the Job Stress Scale, Visual Analogue Scale of Stress, the Insomnia Severity Index, the State and Trait Anxiety Index, the Questionnaire for Emotional Trait and State, the Patient Health Questionnaire, the Quality of Life Enjoyment and Satisfaction Questionnaire, and Gastrointestinal Severity Index were compared at baseline and at the end of the trial period. The primary outcome was a 20% reduction in the PSS score at endpoint. Objective measures included salivary levels of stress biomarkers, including cortisol, α-amylase, immunoglobulin A, lactoferrin, and lysozymes, as well as results of the Test of Attentional Performance. Results: Of the 90 eligible IT specialists, 36 met the inclusion criteria. After the 8-week trial period, significant improvements in self-perceived stress, overall job stress, job burden, cortisol level, general or psychological health, anxiety, depression, sleep disturbances, quality of life, and both positive and negative emotions were found. Conclusion: Our results suggest that PS128TM has the distinct advantage of providing stress relief and can improve mental health for people with a high-stress job. Future placebo-controlled studies are warranted to explore the effect and underlying mechanisms of action of PS128TM. Clinical trial registration: https://clinicaltrials.gov/, identifier: NCT04452253